Novel combination therapy of pedal arch angioplasty and dual distal bypass as an alternative treatment option for vasculitis in patients with chronic limb-threatening ischemia - Nobuko Yamamoto, MD, PhD; Hiroyoshi Komai, MD, PhD; Hideki Sakashita, MD, PhD; Noriyuki Miyama, MD, PhD; Daizo Kawasaki, MD, PhD; Masashi Fukunaga, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
A 68-year-old man with chronic limb-threatening ischemia caused by atypical vasculitis was successfully treated by the combination of pedal arch angioplasty and dual distal bypass. Angioplasty alone failed; therefore, we performed pedal arch angioplasty followed by distal bypass revascularized to the newly created dorsalis pedis artery and posterior tibial artery anastomosis sites. Restenosis occurred twice, and both cases were successfully treated by immediate angioplasty. Both branches of the graft remained patent for >2.5 years, and the wound healed completely. This unique combination of techniques can provide favorable results for selected patients with chronic limb-threatening ischemia.